2016
DOI: 10.1016/j.foodchem.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Development and applicability of a ready-to-use PCR system for GMO screening

Abstract: With the growing number of GMOs introduced to the market, testing laboratories have seen their workload increase significantly. Ready-to-use multi-target PCR-based detection systems, such as pre-spotted plates (PSP), reduce analysis time while increasing capacity. This paper describes the development and applicability to GMO testing of a screening strategy involving a PSP and its associated web-based Decision Support System. The screening PSP was developed to detect all GMOs authorized in the EU in one single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…In terms of qualitative PCR assays, prespotted plates have been effectively used for detection of multiple GMOs in various crop plants [16, 17]. These are plastic plates used in qualitative PCR with primers and probes for selected assays predispensed in wells.…”
Section: Overview Of Different Technologies Used For Gmo Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of qualitative PCR assays, prespotted plates have been effectively used for detection of multiple GMOs in various crop plants [16, 17]. These are plastic plates used in qualitative PCR with primers and probes for selected assays predispensed in wells.…”
Section: Overview Of Different Technologies Used For Gmo Detectionmentioning
confidence: 99%
“…These are plastic plates used in qualitative PCR with primers and probes for selected assays predispensed in wells. Hands-on time is shortened because only one reaction mixture needs to be prepared per sample, which is then distributed over several wells [16]. Element-specific, taxon-specific and event-specific prespotted plates can be prepared and used for the detection of multiple GMOs.…”
Section: Overview Of Different Technologies Used For Gmo Detectionmentioning
confidence: 99%
“…While the cost is influenced by several factors, such as sample type, composition and analytical technology used (Milavec et al 2014), decreasing the number of full quantitative assays has a direct effect on the overall cost. This can be illustrated using the data generated in a recent study (Rosa et al 2016), for which the composition of 135 real-life samples containing GM events was communicated to our laboratory. Results of quantifications performed by laboratories showed that ∼40 % of the GM events were at 0.1 % or not quantifiable (i.e.…”
Section: Practicability and Impactmentioning
confidence: 99%
“…To demonstrate the feasibility of the approach, six maize GM events were chosen based on their frequency of occurrence in EU official samples (Rosa et al 2016). The associated certified reference materials (CRMs) were tested at different GM concentration levels by RTi-PCR for the taxon-and the event-specific assays and Cq signals were then combined to calculate ΔCq values (Cq GM -Cq REF ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, pre-spotted screening and event plates have been developed [34,36] to facilitate the screening and identification of GMOs in food and feed products.…”
mentioning
confidence: 99%